Structural change, productivity growth, and trade policy in Brazil - Firpo, Sergio; Pieri, Renan (International Food Policy Research Institute, 2017)
Throughout the course of only a few decades in the postwar period, the Brazilian economy experienced an intense and fast process of industrialization, which went hand in hand with a major increase in labor productivity and periods of annual growth rates above 10 percent. The rapid growth of the industrial sector was not unintentional. It was driven by a set of policies introduced in the 1950s to protect domestic industries from foreign competition. However, by the early 1980s, these isolationist policies had turned into a curse, with the economy hobbled by high inflation rates and unremarkable economic growth rates.